(untitled) (Global Journal of Management and Business Research, 2014)
Improving the efficiency of budgetary management and preventing overspending that secedes from performance, are fundamental budget stability conditions and issues of strategic importance. "Rulebased" budget means more than merely a stipulation that public finance managements shall observe the rules of budget planning and execution and that the real and budgetary sectors of the economy are characterised by the rule of law. Rule-based budget requires the employment of numerical and procedural regulations by institutionally ensuring their respective observance. Regarding the latter we can declare that in Eastern and Central Europe the interest has grown recently for fiscal councils that have been shooting up like mushrooms and are believed to be almost like "the ultimate weapon" in fighting budgetary overspending. The demands for creating such new institutions at the same time undeniably represent criticism concerning the former processes of the planning mechanisms and their respective institutionalised solutions. This paper aspirations to provide a picture as regards to what extent can fiscal councils be regarded as a new type of organisation within the family of independent fiscal institutions (IFIs), that reflect institutional development and, in the public law of the new democracies having accessed the EU following 2004, mean the best solution to be recommended, i.e. the "best practice".